The Endless Struggle of Man with Plant Viruses - Ladipo, J. L. (Obafemi Awolowo University Press, 2013)
Man has been a struggling being against the menace of viruses on his person, his animals, his crop plants and other plants useful to him from the beginning of history. The skin . lesions on the mummified body of an Egyptian king (Ramese V) who died around 1100 Be at the age of 40 years suggested that he died of smallpox (Good heart; 1969). Before the development of a vaccine against Smallpox, it was one of the world's most devastating human diseases. Those who escaped the fatal effect of the disease invariably had their faces disfigured. Poliomyelitis is another viral disease of man that dates back to the earliest times. The leg deformity of an Egyptian who died about 3000 Be suggested that he must have died of paralytic poliomyelitis (Good heart, 1969). Since the interest in this lecture is not in the struggle of man against viruses that attack him directly, the two examples cited above cue sufficient to show man as a direct. victim of such.